Estratégias para aplicação de fertilizante nitrogenado em capim mombaça - Leal, Matheus Borges (Universidade Federal do Tocantins, 2021)
The potential returns of forage grass in tropical enviroment is great, principaly when the nitrogen fertilization is added in system. So we have a lot of researches to prove that, but not to much about of the fertilizer aplication strategies. This works aim evaluate three parcelament options (two, three and six applications), associated four aplication timing (zero, five, ten and fifeteen days after cut) in mombasa grass with dose of 150 kg N ha-¹, in factorial arrangement, completely ramdomized design, with three replications. The evaluations consisted of: height; agronomic analyzes (Total forage dry mass, leaf dry mass, stalk dry mass, dead material dry mass and stalk leaf ratio). The experiment was conducted in the field conditions on an already established pasture. The timing of the application of nitrogen fertilizer after cutting, as well as the number of parcelaments of the total dose, did not influenced the forage production and the structural quality of the pasture in two crops seasons studied (18/19 and 19/20), in 18/19 season, there was a decrease in mass production for the moment of application 15 days after cutting, without differences up to 10 days after cutting (p < 0,05). However, further studies should be conducted to define a better nitrogen fertilization strategy in cycles.